Simultaneous measurements of X-rays and electrons during a pulsating aurora - Østgaard, N.; Stadsnes, J.; Aarsnes, K.; Søraas, F.; Måseide, K.; Smith, M.; Sharber, J. (CCSD, 1998)
International audience The PULSAUR II rocket was launched from Andøya Rocket Range at 23.43 UT on 9 February 1994 into a pulsating aurora. In this paper we focus on the observations of precipitating electrons and auroral X-rays. By using models it is possible to deduce the electron energy spectrum from X-ray measurements. Comparisons are made between the deduced electron fluxes and the directly measured electron fluxes on the rocket. We found the shape of the observed and the deduced electron spectra to fit very well, with almost identical e-folding energies in the energy range from 10 ke V to ~60?80 ke V. For the integrated fluxes from 10.8 to 250 ke V, we found a discrepancy of 30% . By combining two models, we have found a good method of deducing the electron precipitation from X-ray measurements. The discrepancies between calculations and measurements are in the range of the uncertainties in the measurements.